BIOM-35. MULTI ANALYTE ASSAY FOR NON-INVASIVE DIAGNOSIS OF BRAIN TUMORS. (9th November 2020) - Akolkar, Dadasaheb; Patil, Darshana; Fulmali, Pooja; Puranik, Sneha; Apurwa, Sachin; Patil, Revati; Fulmali, Pradip; Adhav, Archana; Mene, Priti; Paranjape, Pratik; Golar, Snehal; Puranik, Swapnil; et al.
Abstract: The diagnosis of Central Nervous System (CNS) malignancies such as Gliomas in individuals presenting with Intracranial Space Occupying Lesions (ICSOL) is based on histopathological examination (HPE) of tumor tissue obtained by an invasive brain biopsy. However, brain biopsies are resource intensive and are associated with procedural risks such as haemorrhage, morbidity and mortality. The present study evaluated a non-invasive approach for diagnosis of CNS-M in symptomatic individuals based on evaluation of circulating tumor analytes in peripheral blood. The non-invasive multi-platform approach for diagnosis of CNS-M included Immunocytochemistry (ICC) profiling and Fluorescence in situ Hybridization (FISH) of Circulating Tumor Cells (CTCs) and Digital Droplet PCR (ddPCR) of cell-free tumor DNA (ctDNA) and exosomal mRNA. Performance characteristics of each platform were evaluated using blood and tissue samples from 445 individuals including 227 known cases of CNS-M, 47 known cases of benign CNS conditions (CNS-B), 141 known cases of other cancers with brain metastases (OTH-M) and 30 asymptomatic individuals (ASYM). In a set of 37 samples from individuals with radiological ICSOL, suspected of malignancy (CNS-S) complete diagnostic work-up was performed with ICC, FISH and ddPCR. Glial CTCs were detected in 88.8% of 227 CNS-M and undetectable in 89.4% of 47 CNS-B or 100% of 141 OTH-M, indicating high sensitivity and specificity, respectively. The multi-analyte approach discerned CNS-M from CNS-B as well as OTH-M with 91.7% accuracy and accurately inferred lineage in 84.6% of cases. This non-invasive multi-analyte approach can diagnose CNS-M with an accuracy not inferior to standard HPE, can substitute invasive biopsies in most cases and is particularly helpful in cases where a biopsy is not viable.